Serum Adiponectin Level is Lower in Patients with Endometriotic Cyst - Fahdiansyah Fahdiansyah; Ruswana Anwar; setyorini Irianti (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objectives: To analyse the difference of serum adiponectin level between patients with endometriotic cyst and those with non-endometriotic cyst, and its difference between endometriosis stages. Methods: This is a cross-sectional comparative analytical study involving 25 women with endometriotic cyst and 25 women with nonendometriotic cyst, which had undergone laparoscopy or laparotomy surgery. Blood samples were withdrawn and checked for serum adiponectin level in PRODIA laboratory in Jakarta. Serum adiponectin level of both groups were then measured and compared. The study was conducted in Dr. Hasan Sadikin Hospital in September- December 2012. Results: Shows no significant difference in subjects’ characteristic which are age (p = 0.994) and BMI (p = 0.267). There is a significant difference (p < 0.0001) between serum adiponectin level in endometriosis group (mean = 3.91 ± 1.976) with level of which in nonendometriosis group (mean = 8.59 ± 1.977). There is no significant difference (p = 0.384) of serum adiponectin level between stage III endometriosis (mean = 4.24 ± 1.8168) and stage IV endometriosis (mean = 3.54 ± 2.1531). Conclusion: Serum adiponectin level in patients with endometriotic cyst is significantly lower compared to level of which in patients with non-endometriotic cyst. There is no significant difference of serum adiponectin level between endometriosis stages. [Indones J Obstet Gynecol 2013; 1-3: 119-23] Keywords: adiponectin, endometriotic cyst, non-endometriotic cyst, endometriosis stage